Multiple regression analysis of Internet enterprise innovation--Case analysis based on Bilibili - Sun, Zhongmiao (2021 2nd International Conference on Computer Science and Management Technology (ICCSMT), 2021)
In the era of intelligence and big data, the integration of economic development and information technology is becoming closer and closer, and the development of video websites is becoming more and more rapid. Firstly, the main factors affecting the innovation of Internet enterprises were analyzed by establishing a multiple regression model, followed by a case study approach, which mainly selected Bilibili, a typical enterprise of Internet video website, to analyze its corporate innovation. This paper analyzes the business system of Bilibili and studies the innovation of enterprise business model in three aspects: user group, profit model, and user stickiness. The study finds that: improving the incentive of training subjects; expanding the flexible charging space; enhancing participation awareness and retaining core users. Thus, it provides some reference and decision basis for other Internet video website enterprise managers to implement business model strategies.